The politics of parental leave policies : Children, parenting, gender and the labour market - Moss, Peter, 1945-; Kamerman, Sheila B. (Book collections on Project MUSE., 2009)
This title covers 15 countries in Europe and beyond bringing together leading academic experts to provide a unique insight into the past, present and future state of this key policy area.